2011
DOI: 10.1258/td.2011.100410
|View full text |Cite|
|
Sign up to set email alerts
|

Results of infertility investigations and follow-up among 312 infertile women and their partners in Kigali, Rwanda

Abstract: The objectives of this study were to assess the outcome of infertility investigations and an 18-month follow-up of 312 infertile women and their partners in Rwanda. Between November 2007 and May 2009, an infertility research clinic was opened. Infertile couples received basic infertility investigations, the available treatment was provided and couples were followed up over an 18-month period. The infertility remained unexplained in 3%, was due to a female factor in 31%, due to a male factor in 16% or due to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
3
16
0
Order By: Relevance
“…Study conducted by Shamila S et al on risk factors affecting female infertility in South Indian districts of Tamil Nadu and Kerala opine that there was a positive correlation between infertility and menstrual irregularity. 10 In the present study most common menstrual irregularity was oligomenorrhoea which is similar to study conducted by Dhont N et al 11 Conditions associated with female primary infertility most common was Pelvic Inflammatory Disease followed by Polycystic Ovarian Disease. Study conducted by Dhont N et al on also showed that pelvic inflammatory disease was the most common cause of infertility followed by fibroid, PCOD, ovarian cyst and congenital uterine abnormalities.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Study conducted by Shamila S et al on risk factors affecting female infertility in South Indian districts of Tamil Nadu and Kerala opine that there was a positive correlation between infertility and menstrual irregularity. 10 In the present study most common menstrual irregularity was oligomenorrhoea which is similar to study conducted by Dhont N et al 11 Conditions associated with female primary infertility most common was Pelvic Inflammatory Disease followed by Polycystic Ovarian Disease. Study conducted by Dhont N et al on also showed that pelvic inflammatory disease was the most common cause of infertility followed by fibroid, PCOD, ovarian cyst and congenital uterine abnormalities.…”
Section: Discussionsupporting
confidence: 89%
“…Study conducted by Dhont N et al on also showed that pelvic inflammatory disease was the most common cause of infertility followed by fibroid, PCOD, ovarian cyst and congenital uterine abnormalities. 11 Population study of causes, treatment, and outcome of infertility by Hull MG et al revealed failure of ovulation was most common followed by endometritis, coital failure, tubal damage and abnormalities of sperm. 12 Study conducted by Samiha M et al showed most common cause of primary infertility as PCOD followed by genital infection, endometriosis and fibroid.…”
Section: Discussionmentioning
confidence: 99%
“…Because a combined prevention program will likely include suppressive ART for the positive partner [48] or periconception oral or topical PrEP [46, 47, 49, 50, 69], it may be important to base such interventions in a healthcare setting. In addition, because HIV-positive men and women may suffer from infertility [7074], clinical consultation to assess fertility prior to recommending conception strategies will be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown from the articles that infertility males experience the negative effects of infertility diagnosis [18]; the findings suggested that a serious diagnosis of infertility problem could destroy their marriages, and the relationship with community members and a man's prospects of a future father are shattered.…”
Section: Social Impactsmentioning
confidence: 99%